Analisis Strategi Pemasaran dalam Meningkatkan Volume Penjualan UMKM Pasar Cigombong Kecamatan Warungkiara, Kabupaten Sukabumi - Moh Taufik Hidayat; Elan Eriswanto; Sulaeman Sulaeman (AKUNTANSI 45, 2025)
This study utilizes a qualitative research design with a case study approach, applying data source triangulation through observation, interviews, and documentation to identify the strategies adopted by MSMEs in Cigombong Market to increase their sales volume. Data were obtained from both primary and secondary sources, involving seven informants consisting of several shop owners and three consumers to provide a comprehensive perspective on market practices. The results show that MSMEs tend to implement straightforward yet adaptive marketing strategies that respond to current market dynamics, including setting competitive prices, promoting products through informal social networks, and offering personalized services to strengthen customer relationships. The findings also highlight that effective management of marketing resources particularly in distribution, supply availability, and simple logistics arrangements plays a vital role in sustaining business operations amid competition. In addition, some MSMEs have begun adopting basic digital tools, such as WhatsApp and widely used social media platforms, to broaden their promotional reach and communicate with customers more efficiently, all without requiring substantial financial investment. Overall, the study demonstrates that flexible marketing efforts combined with resource-efficient management contribute significantly to supporting the sustainability and growth of MSMEs in traditional market settings.